Evolutionary History of Rhus chinensis (Anacardiaceae) From the Temperate and Subtropical Zones of China Based on cpDNA and Nuclear DNA Sequences and Ecological Niche Model - Liang, Yukang; Zhang, Yang; Wen, Jun; Su, Xu; Ren, Zhumei (Frontiers in Genetics, 2019)
To explore the origin and evolution of local flora and vegetation, we examined the evolutionary history of Rhus chinensis, which is widely distributed in China’s temperate and subtropical zones, by sequencing three maternally inherited chloroplast DNAs (cpDNA: trnL-trnF, psbA-trnH and rbcL) and the biparentally inherited nuclear DNA (nuDNA: LEAFY) from 19 natural populations of R. chinensis as well as the ecological niche modeling. In all, 23 chloroplast haplotypes (M1-M23) and 15 nuclear alleles (N1-N15) were detected. The estimation of divergence time showed that the most recent common ancestor dated at 4.2 ± 2.5 Mya from cpDNA, and the initial divergence of genotypes occurred at 4.8 ± 3.6 Mya for the nuDNA. Meanwhile, the multimodality mismatch distribution curves and positive Tajima’s D values indicated that R. chinensis did not experience population expansion after the Last Glacial Maximum. Besides, our study was also consistent with the hypothesis that most refugia in the temperate and subtropical zones of China were in situ during the glaciation.